Anxiety, depression, and academic stress among medical students during the COVID-19 pandemic - Avila-Carrasco, Lorena; Díaz-Avila, Daisy Lorena; Reyes-López, Adrian; Monarrez-Espino, Joel; Garza-Veloz, Idalia; Velasco-Elizondo, Perla; Vázquez-Reyes, Sodel; Mauricio-González, Alejandro; Solís-Galván, Jorge Alfonso; Martinez-Fierro, Margarita L. (Frontiers in Psychology, 2023)
Abstract: Background: The social distancing policies implemented by health authorities during the COVID-19 pandemic in Mexico and elsewhere led to major changes in teaching strategies for college undergraduates. So far, there is limited data on the impact of the lockdown on the academic stress and mental health in these students. Objective: To assess the presence of academic difficulties, anxiety and depression, and academic stressors causing somatization and coping strategies linked to the pandemic among medical students. Materials and Methods: A cross-sectional study of 728 medical students from years 1 to 5. A questionnaire to assess academic difficulties associated with the pandemic was administered electronically along with the Goldberg anxiety and depression scale, and the SISCO-II inventory on academic stress. Results: Screening for anxiety and depression led to a prevalence of 67.9% and 81.3%, respectively. Most relevant stressors, reported as always/nearly always, included professors’ evaluations (63.9%), and reading overload of academic papers (50.6%). Factorial analyses showed that women were more prone to stress than men (p<0.001). Somatization included drowsiness or increased need for sleep, anxiety, anguish, desperation, chronic fatigue, and sleep disorders. Common coping strategies included practicing a hobby, done always/nearly always by 65% of those with high stress and 34% of those with low stress (p<0.001). Conclusions: There was an important impact of mandatory lockdown during COVID-19 pandemic on mental health of medical students reflected as high prevalence rates of anxiety, depression, and stressors in the studied population. Results point to the need of design and implement preventive strategies to deal with the effects of the online learning modality used during the lockdown.